Ultrasound in EMG‐Guided Biopsies: A Prospective, Randomized Pilot Trial. Issue 4 (15th July 2016) - Billakota, Santoshi; Dejesus‐Acosta, Carolina; Gable, Karissa; Massey, E. Wayne; Hobson‐Webb, Lisa D.
ABSTRACT: Introduction : At our institution, core muscle biopsies are performed on muscles selected using electromyography (EMG). Ultrasound (US) guidance is not used routinely. The aim of this study was to determine if US guidance of EMG selected muscles would increase the diagnostic yield of the biopsy as compared to the current practice standards. Methods: Two trained physicians performed 40 randomized biopsies (US guided or traditional approach). The amount of tissue obtained in each biopsy was recorded (volume and mass), along with the final pathologic diagnosis in each case and incidence of complications. Results : Forty patients were studied. Sixteen muscle biopsies were done with US guidance; 50% had a definitive diagnosis, and 38% did not. In the non‐US guidance group, 58% had a definitive diagnosis, and 33% did not. Conclusions : US did not provide any additive advantage when used to guide biopsy in a muscle previously selected for biopsy with EMG. Muscle Nerve 54 : 786–788, 2016